Risk management and disclosure in Malaysian corporations: managerial perceptions - Mohd Ghazali, Nazli Anum (Inderscience Enterprises Limited, 2012)
The purpose of this study is to examine the extent to which Malaysian companies had established separate risk management committees (RMCs), factors influencing the establishment of RMCs and the type of risks disclosure that should be provided in corporate annual reports. In departure from the majority of prior studies on risk management and disclosure which examined corporate annual reports, the present study sought views from corporate managers through questionnaire survey on issues related to risk management and disclosure in Malaysia. The findings show that 21 (35.6%) companies had established separate RMCs implying that the revised Malaysian Code on Corporate Governance (2007) have had some positive impact on corporate governance in terms of encouraging companies in establishing separate RMCs. Larger companies were expected to establish separate RMCs suggesting that cost considerations have an influence on whether a company would establish a separate RMC. The item under financial risk, 'credit' was rated by the respondents as the most important disclosure.